Perancangan Sistem Informasi Pemberkasan Arsip Dinamis Berbasis Web (Studi Kasus : PT. Griya Indah Persada) - A’lin Aminudin; Thoyyibah Tanjung (CV. Multi Kreasi Media, 2023)
PT. Griya Indah Persada is a company engaged in the housing industry located in South Taangerang City. In filing archives, archiving staff still use conventional methods, namely by storing archive files on a shelf in a special room, searching for files manually, making file records reports using a book, and sending files still using conventional media. Based on these problems, the author provides a proposal by creating a web-based dynamic archive filing information system, so that it is hoped that it can help archive staff in managing existing archives. In this study, the author uses the Extreme Programming method using the Hypertext Preprocessor (PHP) programming language, bootstrap framework and MySQL database. The stages of this research include analysis of the current system, analysis of the proposed system, system design, implementation and testing. With a dynamic archive filing information system, the archive storage process can be done digitally by adding information about the archive, making it easy to find again if needed. In the process of applying information systems, training for archive staff and employees can be carried out in using dynamic archive filing information systems.